ANALISIS PELAKSANAAN PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) DI PROVINSI DKI JAKARTA DAN JAWA TIMUR TERHADAP PEREKONOMIAN NASIONAL - Astuti, Meti (At-Tauzi : Jurnal Ekonomi Islam, 2022)
The Provinces of DKI Jakarta and East Java implement Large-Scale Social Restrictions (PSBB) based on the Regulation of the Minister of Health in PMK RI No.9 of 2020, concerning Guidelines for Large-Scale Social Restrictions (PSBB) in the Context of Accelerating Handling of Corona Virus Disease 2019 (Covid-19). These two regions are the regions with the first and second largest GRDP in the second quarter of 2020 National GDP. Therefore, this study aims to determine the impact of the implementation of PSBB in DKI Jakarta and East Java Provinces on the national economy. This research uses descriptive qualitative research methods. The data sources for this research came from the Central Bureau of Statistics (BPS) and Bank Indonesia (BI). Based on the results of this study, the implementation of the PSBB in DKI Jakarta and East Java had an impact on the contraction of the national economy.